MiR-122 promotes renal cancer cell proliferation by targeting Sprouty2 - Zijie Wang; Chao Qin; Jing Zhang; Zhijian Han; Jun Tao; Qiang Cao; Wanli Zhou; Zhen Xu; Chunchun Zhao; Ruoyun Tan; Min Gu (Tumor Biology)
MicroRNAs are short non-coding RNAs, which have been implicated in several biological processes. Aberrant expression of the microRNA miR-122 has frequently been reported in malignant cancers. However, the mechanism underlying the effects of miR-122 in renal cell carcinoma remains unknown. The aim of this study was to determine the biological function of miR-122 in renal cell carcinoma and to identify a novel molecular target regulated by miR-122. We measured the expression levels of Sprouty2 in six renal cell carcinoma tissue samples and adjacent non-tumor tissues by western blot analysis. We then used reverse transcription polymerase chain reaction to measure miR-122 levels in 40 primary renal cell carcinoma and adjacent non-malignant tissue samples. The effects of miR-122 down-regulation or Sprouty2 knockdown were evaluated via Cell Counting Kit-8 assay, flow cytometry, and western blot analysis. The relationship between miR-122 and Sprouty2 was determined using dual-luciferase reporter assays. Sprouty2 was down-regulated in renal cell carcinoma tissue samples compared with adjacent normal tissue. In contrast, miR-122 was up-regulated in primary renal cell carcinoma tissue samples compared with adjacent normal tissue samples. Down-regulation of miR-122 substantially weakened the proliferative ability of renal cell carcinoma cell lines in vitro. In contrast, Sprouty2 knockdown promoted the in vitro proliferation of renal cell carcinoma cell lines. The spry2 gene could therefore be a direct target of miR-122. In conclusion, miR-122 could act as a tumor promoter and potentially target Sprouty2. MiR-122 promotes renal cell carcinoma cell proliferation, migration, and invasion and could be a molecular target in novel therapies for renal cell carcinoma.